Artificial intelligence for the internet of health things - Shankar, K. (Computer science researcher); Perumal, Eswaran; Gupta, Deepak, Ph.D. (Boca Raton : CRC Press, 2021)
"This book discusses research of Artificial Intelligence for the Internet of Health Things. It investigates and explores the possible applications of machine learning, deep learning, soft computing and evolutionary computing techniques in design, implementation, and optimization of challenging healthcare solutions"--
Artificial Intelligence (AI) for IoHT -- an Introduction -- Role of Internet of Things and Cloud Computing Technologies in Healthcare An Optimal Light Weight Cryptography -- SIMON Block -- Cipher for Secure Image Transmission in Wireless Sensor Networks -- An Extensive Overview of Wearable Technologies in Healthcare Sector -- IoHT and Cloud based Disease Diagnosis Model using Particle Swarm Optimization with Artificial Neural Networks -- IoHT Based Improved Grey Optimization with Support Vector Machine for Gastrointestinal Haemorrhage Detection and Diagnosis Model -- An Effective Based Personalized Medicine Recommendation System using Ensemble of Extreme Learning Machine Model -- A Novel Map Reduce-Based Hybrid Decision Tree with TFIDF Algorithm for Public Sentiment Mining of Diabetes Mellitus -- IoHT with Artificial Intelligence based Breast Cancer Diagnosis Model -- Artificial Intelligence with Cloud Based Medical Image Retrieval System using Deep Neural Network -- Internet of Health Things with Cloud based Brain Tumor Detection using Particle Swarm Optimization with Support Vector Machine -- Artificial Intelligence Based Hough Transform with Adaptive Neuro Fuzzy Inference System for Diabetic Retinopathy Classification Model -- An Internet of Health Things (IoHT) based Intelligent Skin Lesion Detection and Classification Model in Dermoscopic Images -- Internet of Health Things based Image Compression Model using Modified Cuckoo Search Algorithm with Vector Quantization -- An Effective Secure Medical Image Transmission using Improved Particle Swarm Optimization and Wavelet Transform -- IoHT with Wearable Devices Based Feature Extraction and Deep Neural Networks Classification Model for Heart Disease Diagnosis.
OCLC-licensed vendor bibliographic record.
Keywords: Medical informatics; Artificial intelligence -- Medical applications; COMPUTERS / Machine Theory; MATHEMATICS / Arithmetic